Impact of Pharmacy Students on a Level II Trauma Center. Issue 4 (July 2017) - Smith, Lindsey; Samai, Kathryn; Peshek, Stephanie; Kimbrell, Brian
Abstract : This study aims to quantify the benefits of allowing advanced pharmacy practice experience (APPE) students to make medical interventions while on rotation by analyzing their interventions made and the resulting cost avoidance. This retrospective, observational cohort study was completed using self-reported data of APPE student interventions made at a Level II trauma center, under the supervision of a clinical pharmacist. Interventions were analyzed for their impact on patient care and cost avoidance through a comprehensive literature search and online Quantifi reference. A total of 187 interventions over a 7-month study period resulted in an estimated cost avoidance of 26, 175. Advanced pharmacy practice experience students acting as pharmacist extenders resulted in a monthly cost avoidance of 3, 739, which corresponds to 44, 871 per year. Incorporating student pharmacists as active members of an interprofessional team enhanced patient care by increasing medical interventions, leading to increased cost avoidance by optimizing medication regimens.